2006
DOI: 10.1634/stemcells.2005-0319
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Stromal Cells Express a Distinct Set of Biologically Functional Chemokine Receptors

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
476
2
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(516 citation statements)
references
References 63 publications
20
476
2
5
Order By: Relevance
“…However, since MSCs express a range of chemokine receptors, 16 their mobilization probably occur in response to proinflammatory cytokines (such as TNF-␣, interleukin-1) released in response to fracture. 3 TNF-␣ is known to promote mobilization 17 and osteogenic differentiation of MSCs, 18 and absence of TNF-␣ impairs bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…However, since MSCs express a range of chemokine receptors, 16 their mobilization probably occur in response to proinflammatory cytokines (such as TNF-␣, interleukin-1) released in response to fracture. 3 TNF-␣ is known to promote mobilization 17 and osteogenic differentiation of MSCs, 18 and absence of TNF-␣ impairs bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…MSC can also produce a variety of growth factors, cytokines, chemokines and proteases that are likely to play a role either in their immunomodulatory or in their migratory function [29][30][31]. In this respect, MSC have been shown to express a restricted pattern of chemokine receptors, including CXCR4, allowing them to migrate to tissues upon specific chemotactic triggers [32][33][34][35]. These features are likely to represent the basis for MSC homing to multiple organs where they undergo a program of tissue-specific differentiation [36].…”
Section: Immunological Phenotype and Functions Of Mscmentioning
confidence: 99%
“…CXCL6 and CCL20, were up-regulated by LPS in the presence of dlk1. Recently, Honczarenko et al (71) have shown that hMSC cells express certain CC and CXC chemokine receptors as well as their ligands, which have been reported to play a role in controlling the proliferation and differentiation of hMSC (71). The production of chemokines by osteoblastic cells has been demonstrated to play a role in the bone inflammatory response because of infection.…”
Section: Genementioning
confidence: 99%